pVAD-assisted left main DK-Crush Bifurcation PCI Post-ViV TAVR - Das, Anshuman; Planek, Maria Isabel Camara; Attanasio, Steve (Journal of Cardiology and Cardiovascular Medicine, 2021)
We describe successful percutaneous coronary intervention (PCI) of significantly diseased ostial left main (LM) and distal LM bifurcation (Medina 1,1,1) in a patient with a reduced left ventricular ejection fraction and a recent valve-in-valve balloon-expandable TAVR using the DK-Crush technique with the support of a percutaneous left ventricular assist device.